-(w+2)=-4w+11

Simple and best practice solution for -(w+2)=-4w+11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(w+2)=-4w+11 equation:


Simplifying
-1(w + 2) = -4w + 11

Reorder the terms:
-1(2 + w) = -4w + 11
(2 * -1 + w * -1) = -4w + 11
(-2 + -1w) = -4w + 11

Reorder the terms:
-2 + -1w = 11 + -4w

Solving
-2 + -1w = 11 + -4w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '4w' to each side of the equation.
-2 + -1w + 4w = 11 + -4w + 4w

Combine like terms: -1w + 4w = 3w
-2 + 3w = 11 + -4w + 4w

Combine like terms: -4w + 4w = 0
-2 + 3w = 11 + 0
-2 + 3w = 11

Add '2' to each side of the equation.
-2 + 2 + 3w = 11 + 2

Combine like terms: -2 + 2 = 0
0 + 3w = 11 + 2
3w = 11 + 2

Combine like terms: 11 + 2 = 13
3w = 13

Divide each side by '3'.
w = 4.333333333

Simplifying
w = 4.333333333

See similar equations:

| 7+m(-5)=9 | | 4a+6=8-2a | | 5+(-6)+3z=-20 | | 23x+x+3x+(x-7)= | | 5x-4(5x-1)=19 | | 4(x-2)=9x-7-5x | | 10=30x-10 | | x-8.1=4.3 | | 133=x^2-3x+417 | | 20=3x-10 | | x^2-3x+284=0 | | 0.58x-0.43=9.45-3.22x | | y+29=15 | | k(-2)=-6 | | 18x^4-6x^2=0 | | 7-4y=8-7y+3y | | 9(3x+2)=8(6x+4)+3 | | 3[2-4(y-1)]=3(2y+8) | | 3v-2x=15 | | -12x-3=8-2x+6 | | 3x^2-25x-18=0 | | -6y-8=10 | | 2(3t-1)+t=6-t | | -5v+6+3z=-20 | | 10x-4=20x+1 | | 7=4c-5 | | 14+20x=24+18x | | -5v+1x+3z=-20 | | 40-7m=4m-3m | | 14a+3-a+4a+5= | | -2x+20=3x | | 6x-63=4x-3 |

Equations solver categories